A Remark on Isometries of Absolutely Continuous Spaces - Alireza Ranjbar-Motlagh (Journal of Function Spaces)
The purpose of this article is to study the isometries between vector-valued absolutely continuous function spaces, over compact subsets of the real line. Indeed, under certain conditions, it is shown that such isometries can be represented as a weighted composition operator.